Comparison of the effects of different kibble shape on voluntary food intake and palatability of weight loss diets in pet dogs. (June 2019) - Sagols, Emmanuelle; Hours, Marie Anne; Daniel, Ingrid; Feugier, Alexander; Flanagan, John; German, Alexander James
Abstract: Altering characteristics of a dry proprietary diet can increase chewing, slow ingestion speed and reduce voluntary food intake. Panels of healthy research dogs consumed kibbled weight loss diets with either a l round (pastille) or a cross shape. Two panels ('small-size' panel, dogs<10 kg 'all-size' panel, dogs with a range of sizes) were used to determine palatability (study 1), whilst a third panel ('consumption kinetics panel') was used to determine voluntary food intake [VFI] and meal duration (study 2). Study 3 was a field trial where the cross kibble was fed to client-owned overweight dogs undergoing controlled weight loss, and attitudes of owners were sort. In study 1, dogs in the all-size panel consumed more of the cross-kibble diet than of the round-kibble diet ( P < .001), but there was no significant difference in dogs of the small-size panel ( P = 1.000). In study 2, VFI was broadly similar for both diets, with no difference in total consumption across all four meals ( P = .370). However, meal duration was significantly longer for the cross kibble (meal 1: 292 s; meal 2: 650 s) compared with the round kibble (meal 1: 186 s; meal 2: 282, P < .001 for both). In study 3, owners observed more chewing behaviour ( P = .031), slower ingestion speed ( P = .031), and a significant decrease in food-seeking behaviour ( P = .020) when eating the cross-kibble compared with the round-kibble. Altering the kibble shape of a canine therapeutic weight loss diet can decrease ingestion speed without affecting palatability, but studies are now required to determine the effect on outcomes of weight management. Highlights: Dogs consume a cross-shaped kibble more slowly than a round-shaped kibble. Altering kibble shape does not affect palatability in dogs. Owners observe their dog chewing more when consuming a cross-shaped kibble.